Recovery of used acetic acid via sulfuric acid - Raiymbekov, Y.B.; Besterekov, U.; Abdurazova, P.A.; Nazarbek, U.B.; Pochitalkina, I.A. (KU Publ., 2021)
Kazakhstan has a huge phosphate raw material base, where the basis is made up of micro-grained phosphate ores of the Karatau basin. The depletion of reserves of high-quality commercial ores leads to the search for new methods of using the enrichment and sorting of low-grade technogenic ores, one of which is phosphatesiliceous slates. The presented study was carried out in two stages: at the first stage, phosphate-siliceous shales were enriched by the acetic acid method, regime technological parameters, kinetic and thermodynamic regularities of the process were determined. At the second stage of the research a method for recycling used acetic acid during the enrichment of low-grade phosphate-siliceous slates is proposed. In this case, sulfuric acid was chosen as the regenerating agent of acetic acid. The reliability of the performed studies was proved by the use of modern complex research methods: scanning electron microscopy, Energy Dispersive X-Ray and X-Ray difraction analyses. To determine the course of a particular reaction, a thermodynamic analysis was performed using modern HSC 6.0 software. The kinetic data are determined by calculation. The obtained experimental data were subjected to statistical analysis (Chaddock scale, standard deviation, coefficient of determination). The mechanism of interaction of an acetate solution with sulfuric acid is illustratively described. In conclusion, the sulfuric acid method is suitable for the regeneration of applied acetic acid. In this case, a by-product is formed in the form of calcium sulfate. This product can be used as a building binder (confirmed by the protocol of the “National Center of Expertise” of the Republic of Kazakhstan).
Қолданылған сірке қышқылын күкірт қышқылымен регенерациялау
Регенерация использованной уксусной кислоты серной кислотой
Keywords: acid recovery; acetic acid; low-grade phosphorites; beneficiation; sulfuric acid; phosphatesiliceous slates; Chaddock scale; calcium sulfate